Calculation of Rail Internal Impedance by Using Finite Elements Methods and Complex Magnetic Permeability. (5th January 2010) - Dolara, Alberto; Leva, Sonia
Abstract : The internal parameter of UNI 60 rail is calculated by using finite elements methods. Steel's characterizations by its normal magnetization curve and by complex magnetic permeability are here considered and included into the proposed FEM models. Rail's resistance and internal inductance in function of current and frequency are calculated using both FEM and analytical models. The results obtained at the frequency of 50 Hz are compared with few measurements available, and then they are extended to other frequencies.